Intercultural Communication Competence: Its Importance to Adaptation Strategy towards People With Different Cultural Background - Ade Tuti Turistiati (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2016)
This paper presents experiences of a Japanese native speaker who worked as a volunteer teacher in Indonesia. Using data collected through in-depth interview and observation, this study explores, from the Japanese native speaker’s perspective and social interaction between her and Indonesian teachers as well as students. The context of the research is very limited. It examines only one volunteer assigned to teach Japanese language at a senior high school in Bandung for nine months. The result of study shows that the Japanese native speaker experienced culture shock. She had been through the U-curve with these phases: Honeymoon, Crisis, Recovery, and Adjustment. To cope with the culture shock she tried her best to adapt to Indonesian culture.Intercultural Communication Competence:Its Importance To Adaptation Strategy Towards People With Different Cultural Background <w:LsdException Locked=